Perinephric abscess as a rare cause of acute abdomen: A case report - Güler, Yilmaz; Şengül, Serkan; Çalış, Hasan; Uçar, Murat; Özen, Özkan (Journal of Surgery and Medicine, 2020)
Renal and perinephric abscesses are usually confined within the Gerota's fascia and treated with conservatively. We herein present a case with peritonitis caused by the spillage of perinephritic abscess into the abdomen through the Gerota’s fascia, which is clinical outcome. A 41-year-old female patient was admitted to emergency room with complaints of abdominal pain, bloating, fever, and fatigue. During the operation, an abscess of approximately 20x15cm in size was observed to extend into the abdominal cavity through the Gerota's fascia, causing secondary peritonitis. On the 20th postoperative day, the patient was uneventfully discharged. Delay in diagnosis of renal and perinephric abscesses can lead to fatal complications. Laparotomy is a life-saving approach in cases that cannot be treated with percutaneous drainage, when the abscess is large and causes complications such as strictures, fistulas, or secondary peritonitis, by extension through the Gerota's fascia, as in our case.